2020
DOI: 10.1080/10584609.2020.1723752
|View full text |Cite
|
Sign up to set email alerts
|

In Validations We Trust? The Impact of Imperfect Human Annotations as a Gold Standard on the Quality of Validation of Automated Content Analysis

Abstract: Political communication has become one of the central arenas of innovation in the application of automated analysis approaches to ever-growing quantities of digitized texts. However, although researchers routinely and conveniently resort to certain forms of human coding to validate the results derived from automated procedures, in practice the actual "quality assurance" of such a "gold standard" often goes unchecked. Contemporary practices of validation via manual annotations are far from being acknowledged as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 34 publications
2
65
0
1
Order By: Relevance
“…The coefficient was based on the agreement between both coders’ ratings in the pretest. The value obtained for Krippendorff's alpha (0.794) confirmed that the ratings were reliable (Song et al., 2020).…”
Section: Methodsmentioning
confidence: 53%
“…The coefficient was based on the agreement between both coders’ ratings in the pretest. The value obtained for Krippendorff's alpha (0.794) confirmed that the ratings were reliable (Song et al., 2020).…”
Section: Methodsmentioning
confidence: 53%
“…Dictionary-based methods such as AFINN (Nielsen, 2011) can be validated by creating a gold standard dataset (Song et al, 2020). Oolong provides a workflow for generating such gold standard dataset.…”
Section: Semantic Validation Of Dictionary-based Methodsmentioning
confidence: 99%
“…Printing the summary shows Krippendorff's Alpha, an indicator of interrater reliability. The validity metrics of a text analytic method can be tinted by poor interrater reliability of manual annotations (Song et al, 2020). It is important to ensure high interrater reliability first.…”
Section: Trump2mentioning
confidence: 99%
See 2 more Smart Citations